Modality and evidentiality: a discussion of philosophical and formal aspects - Monawar, Monica (Letras de Hoje, 2016)
This work discusses biological, philosophical and formal notions that underlie current approaches on natural language modality. The aim is to promote a theoretical debate of some of the ontological and methodological components that are sometimes taken for granted in current literature on the topic. A discussion on the evolution of language in connection to modality in terms of planning and displacement is promoted, followed by Lewis’s and Stalnaker’s discussions on possible worlds theory. Finally, a comparative approach on Lewis’s and Stalnaker’s perspectives on knowledge and belief is built in order to create a foundation for further readings on the topic of modals and evidentials. ******************************************************************** Modalidade e evidencialidade: uma discussão sobre aspectos filosóficos e formais Resumo: Este trabalho discute noções biológicas, filosóficas e formais que subjazem abordagens atuais acerca da modalidade em linguagem natural. O objetivo deste é promover um debate teórico de alguns componentes ontológicos e metodológicos que são muitas vezes tidos como conhecidos pela literatura atual neste tópico. Uma discussão sobre a evolução da linguagem em conexão com modalidade em termos de planejamento e deslocamento é promovida, seguida pelas discussões de Lewis e Stalnaker sobre a teoria de mundos possíveis. Finalmente, uma abordagem comparativa das perspectivas de Lewis e Stalnaker acerca de conhecimento e crença é construída para criar a base para leituras futuras no tópico de modais e evidenciais. Palavras-chave: Modalidade; Evidencialidade; Filosofia da linguagem; Semântica formal